Reliability of an fMRI paradigm for emotional processing in a multisite longitudinal study. Issue 7 (28th March 2015) - Gee, Dylan G.; McEwen, Sarah C.; Forsyth, Jennifer K.; Haut, Kristen M.; Bearden, Carrie E.; Addington, Jean; Goodyear, Bradley; Cadenhead, Kristin S.; Mirzakhanian, Heline; Cornblatt, Barbara A.; Olvet, Doreen; Mathalon, Daniel H.; et al.
Abstract Multisite neuroimaging studies can facilitate the investigation of brain‐related changes in many contexts, including patient groups that are relatively rare in the general population. Though multisite studies have characterized the reliability of brain activation during working memory and motor functional magnetic resonance imaging tasks, emotion processing tasks, pertinent to many clinical populations, remain less explored. A traveling participants study was conducted with eight healthy volunteers scanned twice on consecutive days at each of the eight North American Longitudinal Prodrome Study sites. Tests derived from generalizability theory showed excellent reliability in the amygdala ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxvs3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.82), inferior frontal gyrus (IFG; <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxvq2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.83), anterior cingulate cortex (ACC; <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxvwn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.76), insula ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxvtm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.85), and fusiform gyrus ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxw16" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.91) for maximum activation and fair to excellent reliability in the amygdala ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxvzp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.44), IFG ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxw58" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.48), ACC ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxw37" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.55), insula ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskxv8b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.42), and fusiform gyrus ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskd8tp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.83) for mean activation across sites and test days. For the amygdala, habituation ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjzskd8wq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Eρ2</alternatives> = 0.71) was more stable than mean activation. In a second investigation, data from 111 healthy individuals across sites were aggregated in a voxelwise, quantitative meta‐analysis. When compared with a mixed effects model controlling for site, both approaches identified robust activation in regions consistent with expected results based on prior single‐site research. Overall, regions central to emotion processing showed strong reliability in the traveling participants study and robust activation in the aggregation study. These results support the reliability of blood oxygen level‐dependent signal in emotion processing areas across different sites and scanners and may inform future efforts to increase efficiency and enhance knowledge of rare conditions in the population through multisite neuroimaging paradigms. Hum Brain Mapp 36:2558–2579, 2015. © 2015 Wiley Periodicals, Inc.